2021
DOI: 10.1038/s41551-020-00662-0
|View full text |Cite
|
Sign up to set email alerts
|

A mathematical model for the quantification of a patient’s sensitivity to checkpoint inhibitors and long-term tumour burden

Abstract: A large proportion of patients with cancer are unresponsive to treatment with immune checkpoint blockade and other immunotherapies. Here, we report a mathematical model of the time-course of tumour responses to immune-checkpoint inhibitors. The model takes into account intrinsic tumour-growth rates, the rates of immune activation and of tumour–immune-cell interactions, and the efficacy of immune-mediated tumour killing. For 124 patients, four cancer types and two immunotherapy agents, the model reliably descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 61 publications
1
29
0
Order By: Relevance
“…These values are depicted in Figure 3 . These results suggest that, while Λ and µ give significantly separated classification ranges for partial/complete response versus stable/progressive disease, the specific value of the binary classification threshold is likely a function of the unique disease-drug combination used, as observed in our prior studies ( Butner et al, 2021 ). This point was explored further through a ‘leave-one-cancer-type-out’ validation study within the calibration cohort, wherein one cancer type was removed from the calibration cohort and used as validation against the parameter ranges in the reduced calibration set obtained from Borghaei et al, 2015 ; Antonia et al, 2015 ; Le et al, 2015 ; Motzer et al, 2015 ; Powles et al, 2014 ; and Topalian et al, 2012 .…”
Section: Resultssupporting
confidence: 57%
“…These values are depicted in Figure 3 . These results suggest that, while Λ and µ give significantly separated classification ranges for partial/complete response versus stable/progressive disease, the specific value of the binary classification threshold is likely a function of the unique disease-drug combination used, as observed in our prior studies ( Butner et al, 2021 ). This point was explored further through a ‘leave-one-cancer-type-out’ validation study within the calibration cohort, wherein one cancer type was removed from the calibration cohort and used as validation against the parameter ranges in the reduced calibration set obtained from Borghaei et al, 2015 ; Antonia et al, 2015 ; Le et al, 2015 ; Motzer et al, 2015 ; Powles et al, 2014 ; and Topalian et al, 2012 .…”
Section: Resultssupporting
confidence: 57%
“…Mathematical modeling is one approach to bridge the scientific knowledge gaps that exist for these interactions. Butner et al 59 , 60 have recently shown in a series of papers that ICI response can be modeled on “super parameters” that describe the “Anti-tumor immune state”, the “tumor cell kill rate” of ICI, and the tumor proliferation rate. The investigators demonstrated that some of these super parameters could be estimated by taking measurements of the tumor volume from standard computed tomography (CT) scans over time, and that these could be used to predict outcomes and long-term benefits of ICI in many solid tumors.…”
Section: Emerging Biomarkers For Immunotherapy In Hccmentioning
confidence: 99%
“…It is was initially suggested that the interaction of radiation and ICI can cause a temporary increase in size and edema where SRS was given prior to ICI in some patients, but other studies with the same histology and agents have not reproduced this, showing instead a gradually declining volume of edema and tumor with response ( 56 , 57 ). A recent paper used a mathematical model of immunotherapy efficacy based on conventional anatomic imaging to examine the response to ICI (ipilimumab and nivolumab) amongst patients with BM from different clinical trials ( 58 ). The BM growth rate at first restaging was as accurate as the retrospective determination of immune response at predicting response, and no additional imaging beyond the clinical structural scans were used.…”
Section: Biomarkers To Predict Responsementioning
confidence: 99%